2011
DOI: 10.31899/rh1.1015
|View full text |Cite
|
Sign up to set email alerts
|

Provider-related barriers to accessing emergency contraception in developing countries: A literature review

Abstract: This report benefitted from the contributions of numerous individuals and institutions. Firstly, I would like to acknowledge the authors of the documents included in this review, as this research would not have been possible without their well-conducted, and documented, program and research activities. I also would like to thank my colleague Martha Brady for her in-depth and substantive contributions to, and conceptualization of, the available evidence with particular regard to repeat use of emergency contrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 45 publications
4
11
0
Order By: Relevance
“…The results also coincide with other countries where studies similarly found moral attitudes among key stake holders and service providers, and showed that ECs fit into young people’s lives [2-4,18]. Due to the sensitivity of the topic, it is possible that some young people, especially those whom we approached in the pharmacies (where there was little opportunity for rapport building), underreported the number of times they had used ECs.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The results also coincide with other countries where studies similarly found moral attitudes among key stake holders and service providers, and showed that ECs fit into young people’s lives [2-4,18]. Due to the sensitivity of the topic, it is possible that some young people, especially those whom we approached in the pharmacies (where there was little opportunity for rapport building), underreported the number of times they had used ECs.…”
Section: Discussionsupporting
confidence: 86%
“…They expressed worries related to negative effects on women’s health, promiscuity, and a fear that young people will forget about condoms in favour of using ECs. Similar concerns have been found among providers in other African and Asian countries, including negative opinions about repeat use, such as the belief that ECs are not meant to be used regularly and can be risky for women’s health [18]. Informally, many service providers in our study mentioned that they only continue to sell the Postpill to young people out of fear of losing clients and thus business.…”
Section: Discussionsupporting
confidence: 71%
“…Doctors' biases reported in earlier literature were confirmed by this study 18 . A majority of doctors oppose ECPs as a prophylactic and as an OTC drug.…”
Section: Discussionsupporting
confidence: 84%
“…Often those opposing OTC sales lack knowledge about the mechanism of action and have a misunderstanding that ECPs induce abortion, or they fear that ECPs may be used for regular contraception and misused by adolescents 16 – 20 . Parents also fear that wide availability of ECPs will increase promiscuous, premarital, and irresponsible sex as well as increase the risk of acquiring sexually transmitted infections (STIs) 18 22 …”
Section: Introductionmentioning
confidence: 99%
“…Stakeholders' support will, to a large extent, determine supply and demand, legality and regulation, awareness of and support for, and public facility distribution, or lack thereof, of EC (Williams 2011). In some countries, EC availability and accessibility have stalled due to groups opposed to FP generally and those who perceive EC as abortifacient.…”
Section: Key Opinion Leaders' Insightsmentioning
confidence: 99%